Half-hearted Inclusivism: The Theological Doctrine of Salvation in the Document of Lumen Gentium and the Fate of Others - Sahertian, Novita Loma; Ming, David; Ichwan, Mohammad Nor (Jurnal Theologia, 2022)
This article examines the salvation concept in the Lumen Gentium document. The concept of salvation in the Christian tradition is based not only on the cross but also on the Lumen Gentium document, which guarantees safety for adherents of religions other than Christianity. This article aims to explain the doctrine of Christian Salvation through the Lumen Gentium document, analyze the debates and variations of views that exist in Christian theology regarding the fate of adherents of other religions, and look at the responses of Christian churches and theologians to these challenges and dilemmas about the fate of others. The approach used in writing this article is an analysis of the literature, which involves the study of theology, the study of ecclesiastical documents, and the study of the views of Christian theologians on soteriology. This article reveals that soteriology emphasizes the importance of explicit faith in Christ as the only way of Salvation stated in Christian teachings. However, there are debates and various views in Christian theology regarding the fate of those who embrace other religions. Some theologians try to embrace religious diversity by arguing that Salvation can be found in other religions through the grace of God working through Christ without explicit knowledge of Him. Meanwhile, some maintain the exclusive view that faith in Christ is the only way to Salvation. Soteriology shows that faith in Christ as the work of Salvation accomplished through His death on the Cross is the core of the Christian understanding of Salvation. But in the context of the fate of others, there are various views in Christian theology. Based on this fact, the inclusivism built by the Lumen Gentium document seems half-hearted. Therefore a healthy theological dialogue and more profound understanding are needed to respond to this complex challenge and to promote an inclusive experience and widespread love for all human beings.